Clinical parameters before and after the transition to dialysis. Issue 2 (17th November 2017) - Maddux, Dugan W.; Usvyat, Len A.; Ketchersid, Terry; Jiao, Yue; Blanchard, Tommy C.; Kotanko, Peter; van der Sande, Frank M.; Kooman, Jeroen P.; Maddux, Franklin W.
Abstract: Introduction: The transition from pre‐dialysis chronic kidney disease (CKD) to post‐dialysis start is a critical period associated with high patient mortality and increased hospital admissions. Little is known about the trends of key clinical and laboratory parameters through this time of transition to start dialysis. Methods: De‐identified data including demographics, vital signs, lab results, and eGFR from the Fresenius Medical Care‐CKD Registry were analyzed to determine trends in clinical and laboratory parameters through the time of transition from 12 months pre‐dialysis start to 12 months post‐dialysis start. Trends in key clinical and laboratory parameters associated with cardiovascular, nutritional, mineral metabolism and inflammatory domains were examined in association with the transition to dialysis start and first year dialysis survival. Findings: All parameters show divergence for patients who survive vs. do not survive the first year of dialysis. Of note, during pre‐dialysis CKD the absolute systolic blood pressure (SBP) level is lower and the slope for SBP decline is significantly steeper for patients who do not survive the first year on dialysis. Discussion: This study uniquely demonstrates the trajectories of key parameters though the transition from pre‐dialysis to post‐dialysis start. Significant differences are noted in the pre‐dialysis period for patients who survive vs. those who do not survive the first year of dialysis. Early recognition of adverse trends in the pre‐dialysis period may create opportunity to intervene to improve early dialysis outcomes.